The Tivoli sustainable neighbourhood: a new way of building the city in Brussels? - Arnaud Bilande; Cynthia Dal; Ludivine Damay; Florence Delmotte; Julie Neuwels; Christine Schaut; Anne-Laure Wibrin (Brussels Studies)
In Brussels and elsewhere, the reference to sustainable development has made its way in public policies. With its 400 housing units, its park and an economic centre dedicated to “green” companies, the “Tivoli” sustainable neighbourhood project is one of the most ambitious projects under way in the Brussels territory. In 2012, researchers from Université Saint-Louis – Bruxelles (USL-B), Université libre de Bruxelles (ULB), Université catholique de Louvain (UCL) and associations such as Periferia – in charge of participation in the Tivoli project – carried out an in vivo study of the project. This article summarises part of the “Quartiers durables” group’s work based on four themes: 1) the reorganisation of public action and “governance”; 2) participation at the heart of the sustainable project; 3) the connections between architecture and the model of the sustainable city; and 4) the appropriation of sustainable living in two other projects in Brussels. For the authors, the Tivoli project reveals (new?) approaches which question more broadly the methods of building the contemporary city.